Surgical management of stage I and II vulvar cancer:The role of the separated incision (Medical Journal of Indonesia, 2003)
Vulvar cancer is a gynecological cancer whose incidence rate is relatively low. Patients generally were admitted at advanced stage, and radiation therapy at advanced stage does not provide favorable prognosis. Two main modalities in the treatment of vulvar cancer are surgery and radiation therapy. However, radiation can be performed in early stage vulvar cancer but surgery is thought to have more benefits, such as in side effect on the ovary/ reproductive function disorder, patient's hygiene factor, and the ease in performing therapy if recurrence occurs. There are various techniques of vulvar cancer surgery, such as radical vulvectomy with butterfly incision (RVBI) and radical vulvectomy with separated incision (RVSI). The objective of this study was to identify the benefits of radical vulvectomy with separated incision in comparison with radical vulvectomy with butterfly incision in terms of the length of surgery, wound recovery, infection incidence, length of hospital stay. This study was a clinical trial performed during the period of 1990-2000. Fifteen cases of vulvar cancer were found and underwent surgery. Fourteen cases were at stage II and 14 cases were histologically defined as squamous-cell carcinoma and 1 case was adenocarcinoma. The average length of surgery in RVSI was 168 minutes, this was shorter than that in VRBI which reached an average of 275 minutes. The incidence of infection in RVSI group was 3 of 11 cases (27.27%), while in RVBI group all cases had infection in surgical wound. Failure of surgical wound approximation was 1 of 12 cases (9.99%), while in RVBI all cases experienced the failure such that cosmetic surgery was required. Length of postoperative care in RVSI group was 12.3 days, while in RVBI 21.5 days. Thus, complications in VRBI were lower, and length of surgery and length of postoperative care were shorter. (Med J Indones 2003; 12: 103-8) Keywords: vulvar cancer, separated incision